Aplicação de técnicas de visualização de informações em uma ferramenta de descoberta de conhecimento - Rosas, Daniel Henrique Perucelli (2013)
Tools for knowledge discovery using data mining to extract information generate reports that are reviewed and may serve as a basis for decision making. But the perception of knowledge gained can be compromised if the results provided by the tools using technical terms, machine language or the display format of the information to be intelligible. Therefore, techniques that use information to display graphics resources become important in knowledge discovery can be applied to the results in order to facilitate the understanding of the information displayed. This work correlates the knowledge provided by the techniques of data mining with graphic features of information visualization techniques in order to assist in the understanding of the results provided by the tools of knowledge discovery. It also presents information visualization techniques most appropriate to convey the knowledge gained in addition to displaying prototypes of graphical representations of the results generated by techniques and algorithms mining tool Weka. The use of visuals to simplify the interpretation of the extracted knowledge and strengthen the information base for decision-making organizations.